Total Synthesis and Stereochemical Reassignment of Mandelalide A. (18th May 2014) - Lei, Honghui; Yan, Jialei; Yu, Jie; Liu, Yuqing; Wang, Zhuo; Xu, Zhengshuang; Ye, Tao
Abstract: The total synthesis of the tunicate metabolite mandelalide A and the correction of its originally assigned stereochemistry are reported. Key features of the convergent, fully stereocontrolled route include the use of a Prins cyclization for the diastereoselective construction of the tetrahydropyran subunit, Rychnovsky–Bartlett cyclization for the preparation of the tetrahydrofuran moiety, Suzuki coupling, Horner–Wadsworth–Emmons macrocyclization, and glycosylation to append the L ‐rhamnose‐derived pyranoside. Abstract : Strukturrevision : Eine revidierte Konfigurationszuordnung des marinen Makrolids Mandelalid A wurde vorgeschlagen und durch Totalsynthese bestätigt. Diese Studie ist eines von mehreren neueren Beispielen, die falsch zugeordnete Strukturen von Naturstoffen durch stereokontrollierte Totalsynthese korrigieren.